Odpowiedzi

2010-02-17T18:57:29+01:00
A) 3/8 * 9/10 * (-16/3) * 10 = 0,375 * 9 * 16/3 = 0,375 * 3 * 16 = 48 * 0,375 = 18
b) 5 * (-0.25)*0,2*(-4)= 1,25 * (-0,8)= -1
c) (-2,5) *0,2*(-10)*2= (-5) * (-2) = -10
d (-6)*(-⁴/₇)*⅖*(-7)*⁵/₁₂= -2,5 * 4 * 2/5 = 1,6 * 2,5 = 4
e) (1½) *0.06*(-⅔)*100 = 6 * (-2/3) * 1½ = -4 * 1½ = -6 (jeżeli przed 1½ był minus to wynik będzie 6.)
2010-02-17T19:17:57+01:00
³/₈ * (-0.9)*(-¹⁶/₃) *10= (-27/80)*(-16/3)*10=9/5*10=18
5 * (-0.25)*0,2*(-4)= -1,25*0,2*(-4)=-0,25*(-4)=-1
(-2,5) *0,2*(-10)*2= -0,5*(-10)*2=5*2=10
(-6)*(-⁴/₇)*⅖*(-7)*⁵/₁₂= 24/7*2/5*(-35/12)=48/35*(-35/12)=-4
(1½) *0.06*(-⅔)*100 = (1½)*(-⅔) *0.06*100 = -1*6=-6

te liczby np. 27/80 to ułamki